2016
DOI: 10.1080/00393630.2015.1131477
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of indoor air quality and the risk of damage to cultural heritage objects using MEMORI®dosimetry

Abstract: Air pollution is one of the environmental influences that degrade cultural heritage objects situated indoors. Other essential influences, such as temperature, relative humidity, and light are often well monitored. The presence of air pollutants is less often measured or included in risk assessment. The MEMORI ® technology presented in this paper was developed as a tool for easy measurement and assessment of the general risk of degradation of heritage objects situated indoors due to indoor exposure to air pollu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 6 publications
1
14
0
1
Order By: Relevance
“…presence of residual salts/ uncarbonized moieties in carbonaceous pigments applied by using the fresco technique) [12,15,16]. Whitening is also reported for bone black [amorphous carbon with apatite Ca 3 (PO 4 ) 2 ] in oil binding medium, possibly related to the photodegradation of the aromatic structure, probably catalysed by lead (present as a siccative, or pigment) [17]. In another study, by the same authors, a variety of issues was identified related to the causes of discolouration of carbon blacks, such as the formation of lead carboxylates from the reaction of the siccative with the binder, or the alteration of lakes present in the mixture, or the degradation of the aromatic carbon compounds.…”
Section: Low Atomic Number (Z) Elements Carbon Blacks (C)mentioning
confidence: 98%
See 3 more Smart Citations
“…presence of residual salts/ uncarbonized moieties in carbonaceous pigments applied by using the fresco technique) [12,15,16]. Whitening is also reported for bone black [amorphous carbon with apatite Ca 3 (PO 4 ) 2 ] in oil binding medium, possibly related to the photodegradation of the aromatic structure, probably catalysed by lead (present as a siccative, or pigment) [17]. In another study, by the same authors, a variety of issues was identified related to the causes of discolouration of carbon blacks, such as the formation of lead carboxylates from the reaction of the siccative with the binder, or the alteration of lakes present in the mixture, or the degradation of the aromatic carbon compounds.…”
Section: Low Atomic Number (Z) Elements Carbon Blacks (C)mentioning
confidence: 98%
“…Huntite and dolomite, Mg-rich carbonates having formula CaMg 3 (CO 3 ) 4 [52]. The attack from polluted water can as well form gypsum CaSO 4 ·2H 2 O and the extremely soluble magnesium sulphate MgSO 4 , and calcite.…”
Section: Chalk Pigments [(Camg)co 3 : Natural/artificial Lime Whitementioning
confidence: 99%
See 2 more Smart Citations
“…Dosimetry as a method of determining air pollution threat was made available by Grøntoft et al [9], under the MEMORI ® system. This consists of two small dosimeter samples; one dosimeter is covered with a thin synthetic polymer film and sensitive to oxidizing gases such as nitrogen dioxide (NO 2 ) and ozone (O 3 ), and with UV light, while the other is a potassium-rich glass sensitive to acidic gases.…”
Section: Introduction and Research Aimsmentioning
confidence: 99%